2015
DOI: 10.1021/acs.orglett.5b02008
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatization Reactions Using Phthaloyl Peroxide

Abstract: A new oxidative dearomatization reaction has been developed using phthaloyl peroxide to chemoselectively install two oxygen-carbon bonds into aromatic precursors. The oxidation reaction proceeds only once; addition of superstoichiometric equivalents of phthaloyl peroxide does not react further with the newly generated 1,3-cyclohexadiene. The reaction has been challenged by the addition of different functional groups and shown to maintain chemoselectivity. Due to the broad reactivity with 1,2-methylenedioxybenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, we have examined the stability of phthaloyl peroxide and demonstrated that this compound is insensitive to direct heating, shock, crush and scrape. Phthaloyl peroxide, which is low shock sensitive and stable below 90 °C, 30 can thus be considered as a relatively safe peroxide reagent, and malonyl peroxides are also insensitive to shock and direct heating. 19 Practitioners should be careful when using phthaloyl peroxide, but its safety concerns should not be exaggerated or misunderstood.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…In addition, we have examined the stability of phthaloyl peroxide and demonstrated that this compound is insensitive to direct heating, shock, crush and scrape. Phthaloyl peroxide, which is low shock sensitive and stable below 90 °C, 30 can thus be considered as a relatively safe peroxide reagent, and malonyl peroxides are also insensitive to shock and direct heating. 19 Practitioners should be careful when using phthaloyl peroxide, but its safety concerns should not be exaggerated or misunderstood.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…In 2015, a novel dearomatative oxidation reaction of 1,3benzodioxole 74 has been developed by Siegel (Scheme 26). [47] As depicted in Scheme 26, phthaloyl peroxide 75 worked as diradical precursor. The O-radical addition towards 74 furnished a cyclohexadienyl carbon-centered radical (78).…”
Section: Dearomatization Reactionsmentioning
confidence: 99%
“…In 2015, a novel dearomatative oxidation reaction of 1,3‐benzodioxole 74 has been developed by Siegel (Scheme ) . As depicted in Scheme , phthaloyl peroxide 75 worked as diradical precursor.…”
Section: Dearomatization Reactionsmentioning
confidence: 99%
“…Cyclic diacyl peroxides act as electrophilic oxidizing agents of electron-rich π-systems. , For example, phthaloyl peroxide 1 and its derivatives are effective in the syn -dihydroxylation of alkenes and the conversion of aromatic compounds to the corresponding phenols (Scheme ). Phthaloyl peroxide 1 was first described as a monomer by Russell in 1955, and its use in alkene oxidation was thoroughly investigated by Greene in a series of elegant studies. Despite this insightful work, exploitation of phthaloyl peroxide as an oxidant was not revisited until 2011 when Siegel and co-workers re-examined the use of 1 in alkene syn -dihydroxylation .…”
mentioning
confidence: 99%
“…Having prepared 4 , we examined its reactivity with a series of nitrogen, sulfur, oxygen, and carbon nucleophiles. While 4 proved less reactive than malonoyl and phthaloyl peroxides, it provided an intriguing reactivity with lithium enolates. Treatment of propiophenone 5 with 1 equiv of lithium hexamethyldisilazide at −78 °C for 30 min followed by addition of a THF solution of 4 and allowing the mixture to react at −78 °C for a further 2 h led to the alkylidene phthalide 6 as a 4:1 mixture of diastereoisomers, the major isomer of which was isolated in 38% yield after chromatography (Scheme ).…”
mentioning
confidence: 99%